Characterization and adsorption studies of Cocos nucifera L. activated carbon for the removal of methylene blue from aqueous solutions - Sharma Y.C.; Uma; Sinha A.S.K.; Upadhyay S.N. (My University, 2025)
Characterization and adsorption characteristics of Cocos nucifera L. activated carbon (CNAC) have been investigated. The activated carbon used in this study was prepared from the coir of C. nucifera L., commonly known as "coconut". The activated carbon was characterized for surface groups and other parameters and was analyzed for pore size distribution. The surface texture of the adsorbent, the pore structure, and the number and position of the functional groups available on its surface for binding methylene blue (MB) were investigated by Fourier transform infrared spectra. X-ray diffraction studies confirmed the amorphous nature of the adsorbent. The activated carbon developed has been used for the removal of MB. Batch adsorption experiments were carried out for the removal of MB onto the activated carbon. The effect of contact time and initial concentration, adsorbent dose, and temperature on the removal of the dye was investigated. A maximum removal of almost 100 % was achieved at 60 mg • L-1 of dye concentration by increasing the adsorbent dose from (3 to 7) g • L-1. Kinetic data were found to fit the first- and second-order kinetic equations, and the values of the rate constants were found to be 0.55 • 10-2 min-1 and 0.082 g • (mg • min)-1, respectively. The resultant equilibrium data were fitted to various isotherm equations. The adsorption capacity of the adsorbent was found to be 15.59 mg • g-1 at room temperature (30 °C). © 2010 American Chemical Society.